Leadership and Followership: Essential Factors for National Development and Achievement of Organizational Goals - Thom-Otuya, Blessing E. N (Mediterranean Journal of Social Sciences, 2012)
Leadership and followership are very essential factors for national development and achievement oforganizational goal. Leadership and followership is a major universal challenge to all nation States; whilesome countries have overcome the primitive or dictatorial stage to propel their economy and social welfareof her people to a comfortable level; other emerging developing economy are still reeling to grow abovethe challenges of impotent leadership and followership syndrome. This paper discussed Leadership from themacro level. It looked into the concept of leadership, Types, qualities, functions and problems of leadershipfrom the Nigeria perspective and the relationship between Leadership and followership. The paper is aimedat enlightening political leaders and their followers of their responsibilities, and promoting goodgovernance in Nigeria. This paper recommend that, leadership and followership relationship should alwaysbe harmonized as to enable the society or group to achieve her vision and set goal. Leadership andfollowership should adopt a new paradigm shift were values, and leadership traits, integrity and otherdiscussed qualities herein will serve as the basis for consideration or conceding Leadership. Consensusselection of leaders should be avoided; Leaders should be elected through democratic and transparentprocess. Tribal sentiments should be set aside in electing and criticizing our leaders. Our target and criteriafor assessment should be our vision and goal as a people.